2020
DOI: 10.1177/2150135119888141
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Homograft Versus Polytetrafluoroethylene Conduits After Neonatal Truncus Arteriosus Repair

Abstract: Background: Despite significant improvement in outcomes with truncus arteriosus (TA) repair, right ventricular outflow tract (RVOT) reconstruction with a right ventricular to pulmonary artery (RV-to-PA) conduit remains a source of long-term reintervention and reoperation. This study evaluated our experience with reintervention in homograft and polytetrafluoroethylene (PTFE) RV-to-PA conduits in neonates. Methods: Primary TA repairs from 2004 to 2016 at a single institution were included. Stratification was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Mercer et al reported a similar performance for bicuspid ePTFE valved conduits with homograft conduits in patients <2 years of age (59). Another study from this team focusing on neonatal truncus arteriosus repair also showed similar durability, with 10-year freedom from replacement of 27.3 and 28.5% respectively for ePTFE valved conduit and homograft conduit (60).…”
Section: The Hand-made Eptfe Valved Conduitmentioning
confidence: 76%
“…Mercer et al reported a similar performance for bicuspid ePTFE valved conduits with homograft conduits in patients <2 years of age (59). Another study from this team focusing on neonatal truncus arteriosus repair also showed similar durability, with 10-year freedom from replacement of 27.3 and 28.5% respectively for ePTFE valved conduit and homograft conduit (60).…”
Section: The Hand-made Eptfe Valved Conduitmentioning
confidence: 76%
“…When analyzed with these criteria, the data from Seese et al suggest that although both conduits had similar outcomes at ten years of follow-up, conduit dysfunction due to stenosis tended to occur earlier in the PTFE group. 6 The data, as presented in the manuscript, may raise some questions. Kaplan-Meier curves demonstrated the same freedom from gradient 40 mm Hg, freedom from reoperation, and freedom from all interventions in the homograft group, namely, 71.4% at eight years.…”
mentioning
confidence: 99%
“…As previously demonstrated by others, 8,9 Seese et al have also found conduit size as a risk factor for earlier failure with a hazard ratio of 1.66 per mm of decreasing graft diameter. 6 Because conduit diameter during primary implantation was smaller in the homograft group, it is reasonable to speculate that this may have at least partially influenced rates and timing for reinterventions.…”
mentioning
confidence: 99%
See 2 more Smart Citations